In vitro evaluation of antibacterial activity in ethanolic extract of whole plant Sphaeranthus indicus Linn. - Sundaresan, Preeja K.; Kesavan, Kala P. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Sphaeranthus indicus Linn is a widely used medicinal plant in Indian traditional system of medicine against human pathogens. Alarming bacterial resistance is urging scientist to search for newer anti-microbial substances from the medicinal plants. The objective of the study was to evaluate the antibacterial activity of ethanolic extract of the whole plant Sphaeranthus indicus Linn (Asteraceae). Methods: The antibacterial activity of ethanolic extract of whole plant of Sphaeranthus indicus Linn was done against Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis and Staphylococcus aureus in Mueller Hinton Agar (MHA) and compared with ciprofloxacin as standard by disc diffusion method. Results: The study revealed that there was no zone of inhibition in doses of 100 mcg, 200 mcg and 300 mcg of ethanolic whole plant extract of Sphaeranthus indicus in MHA plates compared with ciprofloxacin 30 mcg. Conclusions: Ethanolic extract of Sphaeranthus indicus does not have antibacterial activity. Further studies are needed in different extracts and parts of the plant. Simultaneous studies can be done in different places to evaluate environmental factors and regional variations.